Secrecy, Suspicion, Exposure: Negotiating Authority Structures in a Settler Colonial Society as Depicted in Walter Van Tilburg Clark’s The Ox-Bow Incident - Marek Paryż (European Journal of American Studies)
The article discusses the ways in which Walter Van Tilburg Clark’s 1940 novel The Ox-Bow Incident problematizes the issues of secrecy, suspicion, gossip and exposure as a basis for the depiction of a variety of regulatory practices in a hierarchized settler society whose structures of authority enter a phase of renegotiation. The novel can be read as a portrayal of the Far West’s transition toward a more egalitarian and modern social organization. Clark depicts a stratified society in which striving for a form of advancement is a shared necessity that powerfully influences individual mindsets, and this tendency can redefine even the entrenched hierarchies. Secrecy and suspicion exemplify the tactics through which individual interests fuel a larger process of the renegotiation of power relations within the settler collective.